Identification of Stripe Rust Resistance Genes in Common Wheat Cultivars and Breeding Lines from Kazakhstan - Alma Kokhmetova (MDPI AG, 2021)
Stripe (yellow) rust, caused by Puccinia striiformis f.sp. tritici (Pst), is a fungal disease that presents one of the most serious threats to the wheat crops, causing severe yield losses worldwide, including Kazakhstan. The objectives of this study were to: (1) evaluate a winter wheat collection for stripe rust resistance during an adult plant growth stage, (2) identify the presence of selected Yr genes using linked molecular markers in wheat germplasm, (3) identify potentially useful resistant wheat genotypes among leading cultivars and advanced breeding lines. This study evaluated 70 winter wheat genotypes for stripe rust resistance. According to the field reactions, 42 entries (60%) had R or MR reactions including 27 breeding lines (38.6%) and 15 (21.4%) cultivars. Twenty-eight breeding lines/cultivars (40.0%) were susceptible in both years. According to the average coefficient of infection value (ACI) six genotypes were regarded as possessing high level of adult plant resistance. Cultivars/lines carrying Yr10 alone or in combination with other Yr resistance genes provided resistance to stripe rust. Eleven breeding lines showed <5% disease severity in both years. Linked marker analysis revealed the presence of several gene and gene complexes (Yr5, Yr10, Yr15, Yr17/Lr37/Sr38 and Yr18/Lr34). Among a collection of 70 winter wheat breeding lines and cultivars produced in Kazakhstan three stripe rust resistance genes (Yr10, Yr5 and Yr15) demonstrated high frequency occurrence (31.4%, 14.0% and 7.0%, respectively). The most abundant was gene Yr10 identified in 22 genotypes. It was followed by the Yr5 gene, which conferred resistance in 14 lines (20%) and Yr18 gene-11 lines (15.7%). Yr15 was identified in 7 genotypes. Yr17/Lr37/Sr38 gene complex was found in 2 entries. Among 70 evaluated germplasm sources, 42 disease resistant entries are potentially useful resistant wheat genotypes. These carriers of different Yr genes can be used directly in breeding programs to improve stripe rust resistance of winter wheat. Marker-assisted selection can be efficiently applied to develop wheat cultivars with effective gene combinations that would directly assist in developing durable resistance in Kazakhstan.